Upaya Dinas Kesehatan dalam Mencegah Penyebaran Penyakit HIV AIDS di Kabupaten Bungo - Joko Susanto (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
Bungo Regency is one of the autonomous regions in Jambi Province. Bungo Regency is an area that shows rapid development in all fields. These developments have a negative impact which one of these impacts is the rampant drug abuse and covert prostitution. Even though these two factors are the main mediators of the spread of HIV / AIDS. The purpose of this study was to find out about the health service's efforts in preventing the spread of HIV AIDS in Bungo District. The method used in this research is descriptive method with a qualitative approach. In this study the population was the Bungo District Health Office and the Bungo District community as a validity test, the number of samples was 12 informants, consisting of 7 informants from the Health Office and 5 informants from the community.            The data collection techniques are through observation, interviews and document review. Processing data is taken from primary data sourced from interviews, secondary data through theoretical analysis sourced from books, reports, and photographs. The results showed that the Health Service's efforts to prevent the spread of HIV / AIDS in Bungo District through various comprehensive measures, including preventive, promotive, curative, and rehabilitative with broad participation and cooperation involving various sectors and non-governmental organizations and communities has been good enough and has progressed but still needs to be improved so that Bungo Regency can be cleared of HIV / AIDS